Insidensi Ortohantavirus pada Inang Reservoir di Kota Semarang, Jawa Tengah - Septiyani, Rani Dwi; Dhanti, Kurnia Ritma; Kurniawan, Kurniawan; Mulyono, Arief; Handayani, Farida Dwi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Orthohantavirus is an RNA virus that causes Hemorrhagic Fever with Renal Syndrome (HFRS) and Hantavirus Pulmonary Syndrome (HPS). Humans can become infected with orthohantaviruses by inhaling virus particles from the urine, saliva, and feces of infective reservoir hosts. Small mammals from the orders Rodensia, Eulipotyphla, and Chiroptera are the main reservoirs of orthohantaviruses. This study aims to detect and calculate the incidence of orthohantavirus in reservoir hosts in Semarang City. The research was conducted descriptively analytically with a cross-sectional study design. The research population was all mice and shrews in the research location (Gayamsari and Tlogosari subdistricts), and the samples were caught mice and shrews (84). The research was carried out in May-September 2023. Orthohantavirus detection was carried out using the Nested PCR test (pre denaturation, denaturation, annealing and extension). A total of 84 individuals were captured, consisting of Rattus novergicus, Rattus tanezumi and Suncus murinus. Orthohantavirus in this study was successfully detected in Rattus norvegicus. The results of the study showed that the incidence of orthohantavirus in Gayamsari Village was (11.1%), Tlogosari Village (2.78%), and the overall total was (2.38%). It is necessary to control mice to prevent transmission of orthohantavirus.